Efficient Pt(ii) emitters assembled from neutral bipyridine and dianionic bipyrazolate: designs, photophysical characterization and the fabrication of non-doped OLEDs. Issue 41 (25th September 2015) - Hsu, Che-Wei; Zhao, Yongbiao; Yeh, Hsiu-Hsuan; Lu, Chin-Wei; Fan, Cong; Hu, Yue; Robertson, Neil; Lee, Gene-Hsiang; Sun, Xiao Wei; Chi, Yun
Abstract : Pt(ii ) metal phosphor (1 ), with red-shifted emission versus non-planar counterpart (3 ), is particularly suitable for the fabrication of non-doped OLEDs. Abstract : Potential dianionic chelates, 5, 5′-bis(trifluoromethyl)-2 H, 2′ H -3, 3′-bipyrazole (bipzH2 ) and 5, 5′-(1-methylethylidene)-bis(3-trifluoromethyl-1 H -pyrazole) (mepzH2 ), were synthesized from Claisen condensation employing ethyl trifluoroacetate with 2, 3-butanedione and with 3, 3-dimethyl-2, 4-pentanedione, followed by hydrazine cyclization. These chelates were then utilized in the preparation of four emissive Pt(ii ) metal complexes [Pt(tbbpy)(bipz)] (1 ), [Pt(msbpy)(bipz)] (2 ), [Pt(tbbpy)(mepz)] (3 ) and [Pt(msbpy)(mepz)] (4 ), where tbbpy and msbpy represent 4, 4′-di- t -butyl-2, 2′-bipyridine and 4, 4′-dimesityl-2, 2′-bipyridine, respectively. Single crystal X-ray structural analyses of2 and3 were executed to unveil the basic coordination geometry around the Pt(ii ) center as well as the π–π stacking interaction in the solid state. These complexes are essentially non-emissive in solution (Q. Y. = 0.2–0.4%), but are highly luminescent in the solid state with QY of 52% and 83% and τ obs of 368 ns and 8.37 μs for1 and3, respectively. Their photophysical properties were measured and discussed on the basis of computational approaches. For applications, non-doped organic light emitting diodes (OLEDs) were fabricated using1 and3 as emitters, exhibiting red-orange emission with a maximum luminance of 43 000 cd m −2, an EQE of 19.0%, a CE of 21.0 cd A −1 and a PE of 15.5 lm W −1, and yellow emission with a maximum luminance of 5100 cd m −2, an EQE of 7.1%, a CE of 21.0 cd A −1 and a PE of 11.3 lm W −1, respectively. The particularly higher OLED efficiencies of1 versus 3 highlight the design principle of Pt(ii ) based phosphors, particularly for the fabrication of a non-doped OLED architecture.